2018
DOI: 10.1123/ijspp.2016-0797
|View full text |Cite
|
Sign up to set email alerts
|

Mental Fatigue and Physical and Cognitive Performance During a 2-Bout Exercise Test

Abstract: Neither physical nor cognitive performance was affected by mental fatigue, but subjective ratings did reveal significant differences. It is recommended to exclude mentally challenging tasks during the 2-bout exercise protocol rest period to ascertain unaffected subjective test results. This study should be repeated in athletes diagnosed with nonfunctional overreaching/overtraining syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 26 publications
0
31
0
2
Order By: Relevance
“…For example, Marcora et al (2009) found a detrimental effect of mental fatigue on subsequent cycling performance. While the published literature on mental fatigue appears to be rather consistent (but see Vrijkotte et al, 2018), it is important to note that highly cited replication failures on ego depletion stem from preregistered studies with very large samples (e.g. Hagger et al, 2016;Lurquin et al, 2016).…”
Section: Mental Fatiguementioning
confidence: 99%
“…For example, Marcora et al (2009) found a detrimental effect of mental fatigue on subsequent cycling performance. While the published literature on mental fatigue appears to be rather consistent (but see Vrijkotte et al, 2018), it is important to note that highly cited replication failures on ego depletion stem from preregistered studies with very large samples (e.g. Hagger et al, 2016;Lurquin et al, 2016).…”
Section: Mental Fatiguementioning
confidence: 99%
“…The effects of acute physical exercise on the cognitive performances of an adult individual are still under discussion. The existing literature tends to highlight a positive relationship if the exercise is of sub-maximal intensity while the effects seem to be negative for exhaustive exercises [2][3][4][5][6][7][9][10][11]14,15,[18][19][20][21]24,27,30].…”
Section: )mentioning
confidence: 99%
“…Within cognitive processes, there are few studies on the effects of an exhaustive exercise on executive functions. [27][28][29][30][31][32]. This term indicates a set of cognitive processes that allow us to plan, regulate, control, and evaluate behaviors that are useful for achieving a goal [17].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the effects of mental fatigue on MIT performance are controversial, as some have found that mental fatigue is deleterious to MIT performance [39,45], while others have not [7]. For example, studies have found a decrease in the total distance completed by soccer [39] and cricket players [45] during a Yo-Yo test under mental fatigue.…”
Section: Proof-of-principle Of the Mental Fatigue Effects On Mit Outcmentioning
confidence: 99%
“…From a physical exercise perspective, mental fatigue has been associated with a reduced exercise capacity [1][2][3] likely through its effects on cerebral activation [2][3][4] and effort sensation [2,5]. A recent systematic review has confirmed that detrimental effects of mental fatigue on exercise performance have been well evidenced in endurance exercise modes, such as constant workload and time trial exercises [1,3,5]; however, the effects on maximal incremental test (MIT) performance remain poorly investigated [6,7]. This is a relevant aspect, as MIT is a gold-standard protocol, with intensity gradually increased until exhaustion, to assess cardiopulmonary fitness variables, such as maximal oxygen uptake (VO 2MAX ) and ventilatory thresholds [8].…”
Section: Introductionmentioning
confidence: 99%